Observation of coherence in the time-reversed relativistic photoelectric effect - Tashenov, Stanislav; Banaś, D.; Beyer, H.; Brandau, C.; Fritzsche, S.; Gumberidze, A.; Hagmann, S.; Hillenbrand, P.-M.; Jörg, Holger Eric; Kojouharov, I.; Kozhuharov, Ch.; Lestinsky, M.; et al. (Physical review letters, 2014)
The photoelectric effect has been studied in the regime of hard x rays and strong Coulomb fields via its time-reversed process of radiative recombination (RR). In the experiment, the relativistic electrons recombined into the 2p3/2 excited state of hydrogenlike uranium ions, and both the RR x rays and the subsequently emitted characteristic x rays were detected in coincidence. This allowed us to observe the coherence between the magnetic substates in a highly charged ion and to identify the contribution of the spin-orbit interaction to the RR process.
Gesehen am 03.09.2020